2024
DOI: 10.1096/fj.202301454r
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 28A aggravates Con A‐induced acute liver injury by promoting the recruitment of M1 macrophages

Junfeng Zhang,
Dalei Cheng,
Hui Zhang
et al.

Abstract: Immune‐mediated acute hepatic injury is characterized by the destruction of a large number of hepatocytes and severe liver function damage. Interleukin‐28A (IL‐28A), a member of the IL‐10 family, is notable for its antiviral properties. However, despite advances in our understanding of IL‐28A, its role in immune‐mediated acute injury remains unclear. The present study investigated the role of IL‐28A in concanavalin A (Con A)‐induced acute immune liver injury. After Con A injection in mice, IL‐28A level signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 59 publications
(112 reference statements)
0
0
0
Order By: Relevance
“…In a study involving mice injected with Con A, elevated levels of IL-28A were observed. Deficiency in IL-28A was found to limit M1 macrophage polarization by modulating a signaling pathway that inhibits IRF5, consequently reducing the release of pro-inflammatory cytokines such as TNF-α, IL-12, IL-6, and IL-1β from M1 macrophages [83]. Corilagin was shown to effectively inhibit the release of pro-inflammatory cytokines in M1 macrophages by restraining the activation of the IRF5 signaling pathway, providing protection against Con A-induced immune-mediated liver injury.…”
Section: Irfs and Con A-induced Liver Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…In a study involving mice injected with Con A, elevated levels of IL-28A were observed. Deficiency in IL-28A was found to limit M1 macrophage polarization by modulating a signaling pathway that inhibits IRF5, consequently reducing the release of pro-inflammatory cytokines such as TNF-α, IL-12, IL-6, and IL-1β from M1 macrophages [83]. Corilagin was shown to effectively inhibit the release of pro-inflammatory cytokines in M1 macrophages by restraining the activation of the IRF5 signaling pathway, providing protection against Con A-induced immune-mediated liver injury.…”
Section: Irfs and Con A-induced Liver Injurymentioning
confidence: 99%
“…Conjugin A (Con A), a plant lectin isolated from the miller bean (Canavalia ensiformis), was recognized for its role as a T-lymphocyte activator in the immune response to allograft rejection, viral infections or autoimmune disorders in mammals [126]. Con A stimulated the release of a variety of cytokines from immune cells (such as TNF-α, IFN-γ, GM-CSF, IL-2, IL-1β), induced oxidative stress, activated multiple signaling pathways (NF-κB, MAPK, PI3K/PDK1/mTOR, STAT3, and STAT5), and altered the Bax/Bcl-2 ratio, ultimately resulting in severe liver inflammation and hepatocyte apoptosis/necrosis [83,[127][128][129][130]. However, the precise cellular mechanisms underlying liver dysfunction induced by Con A activation remained incompletely understood.…”
Section: Irfs and Con A-induced Liver Injurymentioning
confidence: 99%